Marketing strategies of business systems in global environment - Parkhomenko, Nataliia (Herald of Economics, 2022)
Introduction. The operation and development of business systems in international markets under pressure from competitors requires the application of strategic approaches to marketing management. The lack of a sound marketing strategy in the global environment leads to the loss of competitive positions, financial problems, unprofitable activities, etc. in domestic and foreign markets. Given the fact that in 2021 export and import operations were carried out with 166 partner countries (according to Ukrstat), the validity of the choice of marketing strategy in foreign markets is a very important issue and needs research. The purpose of the article is the process of formation and implementation of marketing strategies of the business systems in a global environment.Methods. In the process of research for the validity of the provisions presented in the article, a set of general scientific and special methods was used, in particular: historical and logical - in the process of studying the theoretical foundations of marketing strategy; analysis and synthesis - to determine the dependence of marketing strategy on the type of market and export products, to determine the relationship between marketing strategy and the degree of coverage of the international market in the global environment; matrix analysis to build a matrix of marketing strategies to enter international markets; process approach - in determining the stages of development and implementation of marketing strategy of business systems in the global environment and the formation of the algorithm of marketing activities in the formation and implementation of marketing strategy of business systems: graphical method - to visualize the results of analytical research; abstract-logical- for theoretical generalization and formulation of conclusions.Results. The article specifies the essence of the concept of «marketing strategy of business systems», considers the dependence of marketing strategy on the type of market and export products. The characteristic of marketing strategies of entering international markets is presented. The relationship between marketing strategy and the degree of coverage of the international market in the global environment is identified. The advantages and disadvantages of marketing strategies to enter international markets are described. The process of development and implementation of marketing strategy of business systems in the global environment is formed. The algorithm of marketing measures in the process of formation and implementation of marketing strategy of business systems is presented.Perspectives. The conducted research creates a basis for further improvement of the methodology of evaluation of strategic marketing alternatives in the implementation of international activities by enterprises.